2017
DOI: 10.1177/0091415016688306
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up on an Appalachian Farm

Abstract: Background Research on centenarians to date has focused on areas with a high population of centenarians. However, there is limited literature on centenarians' perspectives about growing up on farms from the heartland of Appalachia in Eastern Tennessee. Purpose This qualitative descriptive study was designed to characterize the role of a farming childhood by exploring the viewpoints of community-dwelling centenarians who grew up on farms in south central Appalachia. Methods A qualitative descriptive design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…All individuals in the study came from sound economic backgrounds and some of them had been very high achievers and continued to have high cognitive functions at an extreme age. The significance of attainment of a higher education was similar to those in Holston and Callen (2017) and Archer et al (2005), but not identified by Freeman et al (2013). In the Hong Kong study of six centenarians, most participants perceived their working life as the most important factor in their life and retired at very old ages (Wong et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…All individuals in the study came from sound economic backgrounds and some of them had been very high achievers and continued to have high cognitive functions at an extreme age. The significance of attainment of a higher education was similar to those in Holston and Callen (2017) and Archer et al (2005), but not identified by Freeman et al (2013). In the Hong Kong study of six centenarians, most participants perceived their working life as the most important factor in their life and retired at very old ages (Wong et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Our participants commented that they rarely consumed alcohol, and credited this with contributing to their longevity. The qualitative descriptive study on centenarians growing up on an Appalachian farm by Holston and Callen (2017) also put emphasis on eating healthy garden-fresh produce and having ample milk and butter, produced on the farm, as contributing to longevity. For participants in Scelzo et al (2018), who were rural dwelling, 'love of the land' was also a significant factor in the lives of the centenarians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good food was described as part of the fabric of a good family:We always had a pitcher of buttermilk and a pan of sweet potatoes on the table waiting for us when we got home from school. (Holston & Callen, 2017)…”
Section: Synthesis Findingsmentioning
confidence: 99%
“…We always had a pitcher of buttermilk and a pan of sweet potatoes on the table waiting for us when we got home from school. (Holston & Callen, 2017) Looking after your own body included dialogue about whether or not to access formal health care. People described the challenge of deciding, am I ill or is this a natural part of aging?…”
Section: Count Your Blessingsmentioning
confidence: 99%